Prevalence and correlates of physical inactivity among older adults in Malaysia: Findings from the National Health and Morbidity Survey (NHMS) 2015 - Chan, Ying Ying; Sooryanarayana, Rajini; Mohamad Kasim, Noraida; Lim, Kuang Kuay; Cheong, Siew Man; Kee, Chee Cheong; Lim, Kuang Hock; Omar, Mohd Azahadi; Ahmad, Noor Ani; Hairi, Noran Naqiah (Elsevier, 2019)
Malaysia has an increasingly aging population. Despite the substantial benefits of physical activity for healthy aging, older adults are considered the most physically inactive segment of the Malaysian population. The purpose of this study was to determine the prevalence of physical inactivity among older adults in Malaysia and its correlates. We analysed data on adults aged ≥60 years (n = 3790) from the National Health and Morbidity Survey (NHMS) 2015, a cross-sectional, nationwide population-based survey covering information on socio-demographic characteristics, physical activity and other lifestyle-related variables, health conditions, and functional limitations. Individuals included in this study were classified as physically active or physically inactive. Logistic regression was used to determine factors associated with physical inactivity. The overall prevalence of physical inactivity among older adults aged ≥60 years old was 48.8%. Physical inactivity was significantly more prevalent among females, older age groups, Indians, those being single/widowed/divorced, those with no formal education, those who reported high sedentary time (≥7 h/day), those with diabetes, anaemia, and functional limitations (p < 0.001). In fully adjusted analyses, females, older age, high household income (≥MYR4000), inadequate fruits and vegetables consumption (<5 servings/day), high sedentary time, having diabetes, and having mobility impairment were all associated with physical inactivity. Approximately half of the Malaysian older population are physically inactive. Identifying the correlates of physical inactivity among Malaysian older adults will help to develop public health policies and interventions that encourage active living among older people and promote healthy aging in Malaysia.